Biochemistry and Molecular Biology - Brambl, Robert; Marzluf, George A. (The Mycota, A Comprehensive Treatise on Fungi as Experimental Systems for Basic and Applied Research, 2004)
Since publication of the first edition of Volume III in 1996, a number of areas in fungal biochemistry and molecular biology have both expanded and rapidly advanced, especially those areas that incorporate the new resource of genomics. In light of these developments, all the chapters of this new edition have been fully revised and completely updated. Still further, the text now contains eleven new chapters, which cover either new topics or have been written by new contributing authors. The second edition of Volume III includes: Biochemistry and molecular genetics; regulation of gene expression; organelle biogenesis; response factors influencing metabolism; molecular biology of carbohydrates and lignin; molecular aspects of biochemical pathways